Anatomical Studies on Healed Boreholes in Pinus roxburghii Sargent - Lekha, Chander; Sharma, Kulwant Rai (Indian Forester, 2011)
The anatomical studies were conducted on the healed boreholes in Pinus roxburghii which had been tapped with borehole method. Microscopic studies revealed that newly formed callus was a mass of undifferentiated cells and the differentiation of callus cells and formation of traumatic resin ducts were observed in two year old samples. In the initial stage of duct formation, it is a multicellular structure and the formation of lumen in resin duct has been recorded at the transition zone of early wood and late wood in healed portion of borehole. Oleoresin duct was found to be roughly round to ovai in shape.